Trans-scaphoid perilunate fracture dislocation. Case series: Clinical and radiological follow up at 2 years - Pichierri, Paolo; Filipponi, Marco; Pasquino, Andrea; Rollo, Giuseppe; Meccariello, Luigi; Ciatti, Corrado; Valentino, Luigi (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Perilunate dislocations (PLDs) and perilunate fracture-dislocations (PLFDs) are rare, high-energy wrist injuries often associated with diagnostic delays. These complex lesions involve disruption of the carpal bones and ligaments, typically resulting from hyperextension trauma. PLFDs most commonly affect young males and frequently involve the dominant wrist. Early recognition and prompt reduction are crucial to prevent neurovascular compromise and long-term complications. Methods: This retrospective study analyzed 12 cases of surgically treated PLFDs between February 2020 and December 2022. The majority of injuries were due to motorcycle accidents, with scaphoid fractures predominating. Surgical management was tailored to fracture location, employing dorsal or volar approaches, Herbert screw fixation, and strategic K-wire stabilization. Postoperative protocols included immobilization, early physiotherapy, and biophysical stimulation. Clinical outcomes were assessed with PRWE and QuickDASH scores, alongside radiographic monitoring at defined intervals up to 24 months. Results: Most patients achieved fracture union and restored carpal alignment without significant loss of motion or persistent instability. Only one complication—hardware impingement—required revision. Conclusions: The study underscores the importance of early diagnosis, anatomical reduction, and stable fixation to ensure favorable outcomes and minimize the risk of post-traumatic arthritis. Open surgical approaches remain the standard treatment, while minimally invasive techniques require further validation.